ANALYSIS OF APPLICATION OF PSAK NO. 24 ABOUT WORK BENEFITS IN PT. UKINDO BLANKAHAN ESTATE - Yunus, Rusyda Nazhirah (Accounting and Business Journal, 2019)
Employee benefits are rewards given to employees as payment for services that have been provided to companies in improving employee performance and employee loyalty to the company. Employee benefits are given on the basis of the company's obligations to fulfill the rights of workers. Employee benefits consist of short-term employee benefits, post-employment benefits, other long-term employee benefits and termination benefits. Employee benefits provided by the company are discussed and regulated in financial accounting standards, namely PSAK No. 24 regarding employee benefits. In PSAK No. 24 (revised 2013) described employee benefits provided by companies accompanied by recognition, measurement and disclosure of employee benefits to the financial statements. This research uses descriptive qualitative method, the source of data using primary and secondary data. This research was conducted directly by researchers through observation and interviews in order to obtain accurate data. This study aims to determine whether the recording of long-term employee benefits is in accordance with SFAS No. 24 in force. The results showed that the recognition and measurement of long-term employee benefits at PT. UKINDO Blankahan Estate is not in accordance with SFAS No. 24 (revised 2016) applicable and also do not know clearly the recognition and measurement of employee benefits applicable according to PSAK No. 24